Energy Efficiency and Limitations of the Methods of Controlling the Hydraulic Cylinder Piston Rod under Various Load Conditions - Lukasz Stawinski; Justyna Skowronska; Andrzej Kosucki (Energies, 2021)
The article is an overview of various methods of braking and controlling the movement of the piston rod under various load conditions. The purpose of this review is to systematize the state of the art in terms of efficiency, energy consumption and limitations of each method. The article discusses systems with different types of hydraulic actuators, operating under passive, active and variable load during the duty cycle of the piston rod. The existing literature was analysed in terms of applicability, reduction of energy consumption of the systems and even the possibility of energy return. Attention was paid to the costs and the need for additional power sources, as well as the problems and limitations of the presented methods. Based on the simulation model, energy consumption tests were carried out in systems with an actuator loaded with a variable force. There is a comparison of all methods in terms of actuator type, load, energy consumption and the possibility of energy recovery.